Práticas educativas parentais e sua relação com o perfil comportamental e desempenho cognitivo de crianças com transtorno de déficit de atenção e hiperatividade - Marino, Regina Luísa de Freitas (2015)
Parent-child interaction is the most intense relationship of the child in childhood and the parenting practices contribute to their emotional and cognitive development. These relational aspects become even more important when dealing with families of children with Attention Deficit Disorder and Hyperactivity Disorder (ADHD). This disorder is characterized by a persistent pattern of inattention and/ or hyperactivity and impulsivity that interferes with the functioning or development. Children with ADHD often show deficits in executive functions and can present problems in behavioral regulation, with both externalizing and internalizing problems, being more dependent on feedback and monitoring of their parents to regulate their behavior. Thus, the aim of this study was to investigate the associations between parenting practices of caregivers and cognitive profiles of children with ADHD and behavioral profiles of both children and their guardians. The sample comprised 26 children and their caregivers and teachers. The age of the children was between 6 and 16, all diagnosed with ADHD confirmed through an interdisciplinary protocol that provides a neuropsychological, behavioral and clinical assessment for children and adolescents referred with inattention and hyperactivity symptoms. The caregivers responded to Adult Self-Report (ASR), Parenting Style Inventory (IEP), Perception of Family Support Inventory (IPSF), World Health Organization Quality of Life (WHOQOL) - Bref and Child Behavior Checklist for ages 6-18 (CBCL/6-18). The children's teachers responded to the Teacher Report Form for ages 6 – 18 (TRF/6-18). To trace the cognitive profile in terms of children´s executive function performance, we analyzed the Wisconsin Card Sorting Test (WCST) and Conners’ Continuous Performance Test II (CPT-II). Finally, Spearman´s correlation analyses were run between scores of the different scales of the instruments. As a result, it was found that patterns characterized by negative parenting practices were associated with higher frequency of behavioral problems and less adaptive functioning indicators in both children and the caregivers. In contrast, positive parenting practices were associated with appropriate behaviors and adaptive functioning of both caregiver and child. The study also shows that the use of negative parenting practices is associated, in general, with the worst in executive functions abilities, and the reverse is also true. Moreover, it was also possible to demonstrate that negative parenting practices are more often chosen and used by caregivers with low social and family support indicators as well as quality of life, which shows that those responsible have high levels of family conflict. Finally, it was also seen that the caregiver behavior problems are associated with other behavioral problems in children. On the other hand, developed social abilities of caregivers, which characterize a good adaptive functioning, are related to the development of children's social abilities and a good school performance. Therefore, these results reinforce the importance of considering the family in the treatment of children with ADHD, as well as in preventing the worsening of symptoms.